SOSIAL BUDAYA MASYARAKAT ISLAM ACEH: STUDI INSTITUSI DAYAH MODERN ULUMUDDIN. - Ridwan Muhammad Hasan; Jasafat (STAI Nusantara Kota Banda Aceh, 2026)
Education is a process of achieving transformation, both within oneself and within the community. Therefore, a proper educational process liberates individuals from various forms of intimidation and exploitation. This is where the affinity of paidagogy lies, namely, comprehensively liberating individuals from external constraints, or what might be considered to be something that restricts a person's freedom. Therefore, the modern dayah institution is a very significant element in living life, both socially and culturally. Throughout human history, education has been a barometer for achieving the maturity of life's values. The modern dayah institution is an educational institution that has been embedded in the journey of Indonesian society for hundreds of years. It is a unique institution with its own unique characteristics that are unlike any other form of education.